Tecnologías Opacas - Parra Cancino, Juan; II Congreso Latinoamericano de Práctica Artística como Investigación Pontificia Universidad Católica de Chile October 2-4, 2024 (2023)
guitar, electronics and networked trumpet
Keynote Lecture, and performance for the faculty and Students of the Catholic University, Chile
FRIS
Editorial review
Keywords: Music, Thought and Technology